The effect of Slaughter Weight on Organ and By-product Weights of Pigs - Sonaiya, E. B. (Faculty of Agriculture, University of Ife, 2015)
The effect of slaughter weight on organ and by-product weights in pigs was determined by slaughtering 101 pigs at six slaughter weights ranging from 22 to 97kg. Slaughter weight had a highly significant influence on the weight of all organs and by-products such as liver, spleen, kidney, heart, hair, skin, head, blood, bone and kidney fat. Heavier slaughter weights above 74kg appear more advantageous in terms of the amount of by-products obtained but also .produced excessively fat carcasses. Breed and sex had no significant effect on organ and by-product weights. The proportion of organs declined while non-organ by-products increased with increasing body weight. The utilisation of abattoir by-products for food, feed and as industrial raw materials has the potential to increase the profitability of pig production.